Annual review of comparative and international education 2013 - Wiseman, Alexander W., 1968-; Anderson, Emily (International perspectives on education and society ;, 2013)
This inaugural volume is a forum for stakeholders and scholars to examine current trends and identify future directions in comparative and international education, using several essays as a context for discussion and analysis. Contributors address the questions and themes discussed in these essays including: the use of new conceptual or methodological frameworks; the role of CIE in teacher education and higher education; the emergence of new area studies, and diversification of the field to include human rights. The volume provides an analytic overview of published work in the field, with discussions of education theory, policy and practice. Chapters in this annual review both highlight the strengths in the field as well as the exciting and up-and-coming developments in theory, method, practice, and research. This annual review will bring together both scholars and stakeholders in the field to highlight those developments of particular relevance to contemporary and future educational reform and school/classroom applications.